Corrosion behavior of nitrogen alloyed martensitic stainless steel in chloride containing solutions. (15th May 2017) - Qi, Xing; Mao, Honghuan; Yang, Yitao
Highlights: Nitrogen bearing experimental steels possess more superior corrosion resistance. An optimum range of nitrogen contents is discovered. Nitrogen and carbides are the main factors influencing the corrosion properties. An underlying mechanism for evolution of corrosion behavior is proposed. Abstract: Influence of nitrogen alloying on corrosion resistance of martensitic stainless steels (MSSs) with different nitrogen contents was investigated by immersion corrosion measurement and electrochemical measurement in chloride medium. It was observed that the nitrogen bearing MSSs exhibit more superior corrosion resistance, and an optimum range of nitrogen content between 0.04-0.05 wt% was found. The degradation of corrosion properties happened in higher nitrogen bearing samples is attributed to the occurrence of more concentrated Cr-depleted zones resulted from massive Cr-rich M23 C6 carbides precipitation, although nitrogen addition is believed to be able to improve the corrosion resistance of MSSs effectively.